Measuring Soil Water Content with Ground Penetrating Radar: A Decade of Progress - Klotzsche, A (2020)
Tremendous progress has been made with respect to ground penetrating radar (GPR) equipment, data acquisition, and processing since the establishment of GPR as a tool for soil water content determination in vadose zone hydrology about 25 yr ago. In this update, we aim to provide a critical overview of recent advances in vadose zone applications of GPR with a particular focus on new possibilities for multi‐offset and borehole GPR measurements, the development of quantitative off‐ground GPR methods, full‐waveform inversion of GPR measurements, the potential of time‐lapse GPR measurements for process investigations and hydrological parameter estimation, and recent improvements in GPR instrumentation. We hope that this update encourages the soil hydrology, groundwater, and critical zone community to embrace GPR as a viable tool for soil water content determination and the elucidation of subsurface hydrological processes.